PERANCANGAN KAPAL GENERAL CARGO 6200 DWT KECEPATAN 10 KNOT DENGAN RUTE PELAYARAN BANJARMASIN - SEMARANG - Muhammad Iqbal Ramdani, (2020)
General cargo ship is a ship that carries cargo of goods that have been packed. General cargo ships play a role in the process of shipping goods from one country to another as well as shipping from one island to another in a country. This research was made to design a 6200 DWT cargo ship with a speed of 10 knots for the Banjarmasin - Semarang shipping route. This design ship is to support the government's program in the concept of sea tolls so that the distribution of goods is evenly distributed in every region in Indonesia. Banjarmasin with commodity in the form of rubber requires a wider market and also to meet the needs of other regions that do not produce rubber in the region. And vice versa, Banjarmasin requires goods from other regions which are usually in the form of convection goods, food, such as sugar and flour, then abundant building materials on the island of Java. The method of this design is to use two comparative vessels to find the size of the principal to be designed. The design of the ship is carried out in several stages, such as making general plans, line plans, hydrostatic analysis, ship resistance analysis, ship stability, and others. Keywords: General Cargo Ship, cargo, Semarang, Banjarmasin, Sea Tol